Sincelejo city water reservoirs. A view from sustainability: Sincelejo city water reservoirs. A view from sustainability - Martínez Osorio, Gilberto (Corporación Universitaria del Caribe, CECAR., 2019)
This article condenses the results of an investigation on the correspondence between the old water management devices of the city of Sincelejo, Sucre, Colombia, with the sustainable water management systems of today. The aim of this paper is to demonstrate that, in the urban architectural complex built during the first half of the 20th century, which is currently recognized as the Historical Town of Sincelejo, there were practices that fit in with current perspectives of sustainable and self-sufficient water management; These practices can be taken up again as an alternative, in view of the difficulties of the aqueduct system and it’s not very promising projections, as a result of the overexploitation to which the Morroa aquifer, the only source of water supply in the Savannah region of the Department of Sucre, is exposed. The work was supported by a comparative analysis between the technical characteristics of the past cisterns, which were raised and catalogued, and the concepts of sustainable water management, which were accessed through a bibliographic review in databases and libraries.